Morphogenetic and structural characteristics of andropogon grass submitted to different cutting heights Características morfogênicas e estruturais do capim-andropógon submetido a diferentes alturas de corte - Sousa B.M.D.L. (2010)
This work was performed aiming to evaluate the morphogenetic and structural characteristics of Andropogon gayanus cv. Planaltina species submitted to three cutting heights (20, 27 and 34 cm). The three cutting heights were allocated in experimental units (12 m2) in a complete randomized block design with three replications. The cuts were done when the light interception by the sward reached 95%. At this moment, the sward height revealed itself constant with values close to 50 cm. The lowest cutting height (20 cm) influenced negatively the final leaf blade length, the number of live leaves, the leaf lifespan, the stem elongation rate and the tiller population density, and it influenced positively the phyllochron and the leaf senescence rate. Probably, cuts at 20 cm height caused a high decapitation and death of the tillers. The worst growth conditions in addition to the blossom of this specie occurred during fall resulted in higher stem elongation rates and number of live leaves, and lower phyllochron, final leaf blade length, and leaf lifespan. The sward height can be used as a practical and efficient criterion in the management of andropogon grass. Under intermittent management conditions, the regrowth of andropogon grass must be interrupted when the sward reaches 50 cm height, and the defoliation must be interrupted when the stubble height is close to 27 cm. © 2010 Sociedade Brasileira de Zootecnia.